YOUNG GENERATION’S PERCEPTION OF SMALL-TOWN DEVELOPMENT IN THE LAST TEN YEARS IN KALIANDA DISTRICT SOUTH LAMPUNG REGENCY - Ratu Nabillah (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2021)
The dichotomy of